Mazhab Idealisme Konsep Dan Penerapan Pedagogik Dalam Pembelajaran - Aulia Rezkyana Agus; Sudarni Sudarni; Idawati Idawati (Journal on Education, 2025)
This study aims to look at the application of the school of idealism in education in Junior High School. This research uses the observation method with a focus on teachers' daily behavior, relationships with peers, and professional behavior. This research was conducted in one of the schools in Makassar. The results show that teachers in the school apply the school of idealism in their education. This can be seen from their daily behavior, where teachers in the school show behaviors that indicate that they have high spiritual and moral values. They also exhibit behaviors that show they care about others and the environment. In relationships with peers, teachers in these schools show harmonious relationships and support each other. They also share knowledge and experiences to improve the quality of learning. On teachers' professional behaviors, teachers in these schools exhibit behaviors that show they have a high commitment to education.